Harmonisasi Kerangka Pengaturan Pajak Karbon di Indonesia dengan Carbon Border Adjustment Mechanism Uni Eropa: Studi Komparatif untuk Menghadapi Hambatan Perdagangan - Atiek Pratiwi Putri Naue (Lembaga Yasin AlSys, 2026)
The urgency of implementing a carbon tax in Indonesia has reached a crucial point amid increasing global environmental degradation and international demands for industrial decarbonization. In this context, the carbon tax is viewed not only as a new source of state revenue, but also as a manifestation of the state’s responsibility to protect the right to a good and healthy environment as mandated by the constitution. This study aims to analyze legal uncertainty in the regulation of the carbon tax in Indonesia and to formulate a more ideal regulatory model through a comparison with the European Union’s Carbon Border Adjustment Mechanism (CBAM) framework. This study used a normative juridical method with a statutory approach through an examination of the UU HPP and UU HKPD, a conceptual approach grounded in the doctrine of the welfare rule of law and the theory of trias politica, and a functional comparative approach to the European Union CBAM regulation. The results showed that Article 13 of Undang-Undang Nomor 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan still leaves a gap of legal uncertainty due to the absence of rigid technical regulations as well as the existence of a policy contradiction between the ease of doing business under the UU Cipta Kerja regime and the demands for environmental protection, which should be mandatory for carbon-based industries. The research findings emphasize that Indonesia requires a policy reorientation through cross-sectoral regulatory harmonization to internalize the cost of carbon externalities into the production price structure fairly through a dynamic and competitive tariff model. This study concludes that strengthening a nationally integrated digital Monitoring, Reporting, and Verification (MRV) system and adapting a domestic carbon border adjustment mechanism are strategic steps to improve the effectiveness of the carbon tax. The contribution of this study lies in its conceptual offering regarding the strengthening of fiscal instruments and juridical protection for national industries in facing increasingly stringent global green standards, while at the same time reinforcing the direction of Indonesia’s environmental and trade policy.